LANGUAGE MEANS EXPRESSING THE MEANING OF "RESPECT" IN THE ENGLISH AND UZBEKI LANGUAGES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
The emergence of researches on language means expressing "respect" which are researched within the framework of comparison and pragmalinguistics in the linguistics of the peoples of the world at present serves to deepen the understanding of the peculiarities of speech issues. Speech units serve as language tools to express a certain meaning. Below is an opinion about the language means that express the meaning of "respect" in English and Uzbek languages.